Expanding medicaid coverage for early treatment of HIV-positive persons and implications for poverty reduction / Gabriel Tourek - Tourek, Gabriel (Universiti Teknologi MARA, Kedah, 2011)
This paper offers Medicaid assistance for early HIV/AIDS treatment as a case study in reform of the status quo administration of Federal and state health systems and undertakes to provide a compelling case for early care to lowincome individuals with health needs. Since the outbreak of HIV/AIDS in the United States in the early 1980s, Medicaid (and Medicare) eligibility requirements restrict benefits to HIV-positive individuals who are completely incapacitated while access is deferred for those struggling in the interim before severe disability. De facto, HIV-positive Medicaid recipients – low-income sufferers and the majority of infected persons of color –experience shorter life expectancies and lower qualities of life than their privately-insured counterparts. Interventions addressing HIV-related illness among poor populations may also address an underlying cause of their low earnings, removing a barrier to work and encouraging employment by improving physical and emotional capacities as well as future life prospects.